PPP/PFI - Konsep, Pelaksaan & Cabaran (Concept, Implementation & Challenges) - Abdul Rashid, Khairuddin (2015)
The presentation focuses on PPP/PFI. It is for a training programme "Pengurusan Kontrak & Pembiayaan Projek Kerajaan" or "Contract Administration & Project Funding in the Public Sector" for senior Malaysian civil servants .